Toward a Rich Data Future for School Finance Research. (November 2019) - Baker, Bruce D.; Chingos, Matthew M.
This special topic is intended to advance research in school finance using two newly produced compilations of multiple longitudinal data systems, the School Finance Indicators Database (http://schoolfinancedata.org/ ) and the Urban Institute, Education Data Explorer (https://educationdata.urban.org/data-explorer/ ). This special topic contains two articles taking advantage of comprehensive longitudinal data on school finance. The first, by Victoria Sosina and Ericka Weathers, uses panel data from the School Finance Indicators Data System from 1999 to 2013 to evaluate whether and to what extent changes to Black-White and Latinx-White demographic differences among districts leads to greater resource disparity over time. The second article, by Knight and Mendoza, combines data from the Census Fiscal Survey with data from the California Department of Education to explore whether differences in data on and measures of school funding equity matter (i.e., lead to similar or different conclusions) when evaluating the effects of California's 2013 adoption of the Local Control Funding Formula.